PENENTUAN MODEL PENILAIAN HARGA JUAL PRODUK PERUMAHAN TIPE MENENGAH KE ATAS DENGAN ANALISIS STATISTIK REGRESI (Studi kasus wilayah Banjarbaru dan Surabaya) - Ferra Maryana; Ferli Erwansyah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
This study aims to made property valuation by regression analysis was applied to medium- to middle-class homes above in the Banjarbaru and Surabaya regions, to obtain a regression model best use software Minitab 19 with variables that can influencing namely land area, building area, number of rooms, number of rooms bath, number of floors, location, ownership certificate, garage and garden. Results research shows that there are differences in influencing factors selling price of houses in Banjarbaru and Surabaya.